Analysis of knee joint movement when using Alpine skis of different width and the related risk fators for injury - Zorko, M.; Lesnik, B.; Kolman, K.; Supej, M. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aim of the study was to establish differences in positions of the knee joint of competitive skiers during a ski turn using skis of different width. Our hypothesis was that knee joint abduction and external rotation increase as the width of the ski increases.